2008
DOI: 10.1038/ijo.2008.195
|View full text |Cite
|
Sign up to set email alerts
|

SNP analyses of postprandial responses in (an)orexigenic hormones and feelings of hunger reveal long-term physiological adaptations to facilitate homeostasis

Abstract: Background: The postprandial responses in (an)orexigenic hormones and feelings of hunger are characterized by large interindividual differences. Food intake regulation was shown earlier to be partly under genetic control. Objective: This study aimed to determine whether the postprandial responses in (an)orexigenic hormones and parameters of food intake regulation are associated with single nucleotide polymorphisms (SNPs) in genes encoding for satiety hormones and their receptors. Design: Peptide YY (PYY), gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 49 publications
(51 reference statements)
0
0
1
Order By: Relevance
“…Ratings of fullness and prospective food consumption were found to be different between the genotype groups for LEP with a significant increase in feelings of fullness and suppressed prospective food consumption in AA homozygotes relative to G carriers. This is in contrast with the two studies by den Hoed et al ( 26 , 32 ) , in which LEP was not associated with hunger and satiety ( 26 ) and where GG homozygotes felt more hungry compared with GA, but not AA individuals ( 32 ) . Additionally, den Hoed et al ( 26 ) showed that AA individuals had lower hunger ratings compared with carriers of the risk allele in LEPR , while in the present study, there was no effect of LEPR on appetite.…”
Section: Discussioncontrasting
confidence: 97%
“…Ratings of fullness and prospective food consumption were found to be different between the genotype groups for LEP with a significant increase in feelings of fullness and suppressed prospective food consumption in AA homozygotes relative to G carriers. This is in contrast with the two studies by den Hoed et al ( 26 , 32 ) , in which LEP was not associated with hunger and satiety ( 26 ) and where GG homozygotes felt more hungry compared with GA, but not AA individuals ( 32 ) . Additionally, den Hoed et al ( 26 ) showed that AA individuals had lower hunger ratings compared with carriers of the risk allele in LEPR , while in the present study, there was no effect of LEPR on appetite.…”
Section: Discussioncontrasting
confidence: 97%